Cyprus University of Technology, and the Cyprus Ministry of Education and Culture - (:unkn) unknown (My University, 2026)
Through the Roadblocks: Realities in Raw Motion Conference co-organized by NeMe, the Department of Multimedia and Graphic Arts (Art History and Theory Research Lab) of the Cyprus University of Technology, and the Cyprus Ministry of Education and Culture. “The Persistence of the Image” Gabriel Koureas CY/UK, Klitsa Antoniou CY Publication Available